The China-EU BIT: The emerging 'Global BIT 2.0'? - Wenhua Shan; Lu Wang (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2014)
The China-EU BIT currently being negotiated may be the "Global BIT 2.0," given that it will be the first new generation BIT that the EU and China conclude on their own initiative and is likely to significantly impact BIT practice worldwide.
Keywords: 330